2009
DOI: 10.1103/physrevlett.103.226803
|View full text |Cite
|
Sign up to set email alerts
|

First Direct Observation of a Nearly Ideal Graphene Band Structure

Abstract: Angle-resolved photoemission and X-ray diffraction experiments show that multilayer epitaxial graphene grown on the SiC(0001) surface is a new form of carbon that is composed of effectively isolated graphene sheets. The unique rotational stacking of these films cause adjacent graphene layers to electronically decouple leading to a set of nearly independent linearly dispersing bands (Dirac cones) at the graphene K-point. Each cone corresponds to an individual macro-scale graphene sheet in a multilayer stack whe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
428
2
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 445 publications
(458 citation statements)
references
References 32 publications
26
428
2
2
Order By: Relevance
“…The complex interlayer atomic interactions indicate that the low-energy expansion about the K point is not suitable in obtaining energy dispersions; therefore, the effective-mass model can not be used to achieve further magnetic quantization. The three zero-field pairs of energy bands contain oscillatory, sombreroshaped and parabolic dispersions, which could be examined by ARPES [82]. They are magnetically quantized into three groups of LLs, defined by the dominating subenveloped functions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The complex interlayer atomic interactions indicate that the low-energy expansion about the K point is not suitable in obtaining energy dispersions; therefore, the effective-mass model can not be used to achieve further magnetic quantization. The three zero-field pairs of energy bands contain oscillatory, sombreroshaped and parabolic dispersions, which could be examined by ARPES [82]. They are magnetically quantized into three groups of LLs, defined by the dominating subenveloped functions.…”
Section: Resultsmentioning
confidence: 99%
“…The special band structure could be verified by angle-resolved photoemission spectroscopy (ARPES) [82]. The LL evolution under a magnetic field reveals a complex pattern of LL anticrossings and splittings, as a result of the specific interlayer atomic interactions derived from the full tight-binding model.…”
Section: Introductionmentioning
confidence: 97%
“…[7][8][9] The latter with rotationally stacked layers exhibits properties similar to SLG. [10][11][12] Moreover, it shows improved charge carrier mobility. 13 Furthermore, it has been observed that the rotationally stacked BLG decouples its electronic structure and preserves the intrinsic properties of SLG.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental graphene sample is synthesized by using three di erent methods. The rst type is multilayer epitaxial graphene (MEG), where the individual layers are electronically decoupled due to their unique rotational stacking, and each layer exhibits a single graphene layer Dirac cone near the Dirac point so that MEG behaves in essence as multilayer graphene [111,112]. The second type is singlecrystal CVD graphene (sCVDG), which is grown on oxygen-rich copper foil into large individual single crystals exceeding hundreds of micrometers in size [113].…”
Section: Optical Pump and Thz Probe DI Erential Transmission Spectramentioning
confidence: 99%